STRATEGY AND IMPLEMENTATION OF SUSTAINING E-CUSTOMER LOYALTY TO SHOPEE USERS IN EAST JAVA - Vitasari, Prima; Maziyah, Nurul; Fuad Achmadi; Hadi, Eko Kusuma; Akidin, Lulud; Haki, Zulfani (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2024)
The digital economy is growing, especially in the field of e-commerce. Indonesia as one of the countries that has a great opportunity for the growth and development of e-commerce. This research conducted a study on Shopee e-commerce as the most popular marketplace to create strategies and implementations to maintain consumer loyalty. A total of three hundred and ninety-three customers participated in filling out the survey questionnaire. Data collection through surveys using google form for questionnaires. The survey results are used as a reference for making strategies that are then implemented to maintain consumer loyalty at Shopee. Improve and improve service quality, especially in privacy indicators. Responses from consumers show that privacy, responsiveness, and contact are leading indicators that need to be considered in making service improvement strategies. Furthermore, the strategy made is to improve and improve service quality, especially on privacy indicators, with Shopee needing to explain the privacy policy in an attractive visual form such as a slideshow that cannot be skipped every time a user logs in. Responsiveness, Shopee provides convenience for return options that are not suitable, Shopee handles returns well, Shopee offers a guarantee for the goods provided, Shopee tells what to do if my order is not processed, Shopee is able to overcome problems in transactions well. Contact, Shopee should improve service quality by being more responsive and fast to handle customer complaints and questions on social media. The implementation of improvements is recommended to Shopee so that it is better in service and satisfies consumers